Tokens: the cognitive significance - Schmandt-Besserat, Denise (Documenta Praehistorica, 1999)
Media shape the mind of those who use them. I analyze how tokens used for counting and accounting in prehistory brought people to thinking in greater abstraction.
Keywords: archaeology; arheologija; arheološke najdbe; neolitik; žetoni; mediji; communication medium; ideogrami